2018
DOI: 10.1080/17470218.2017.1310269
|View full text |Cite
|
Sign up to set email alerts
|

Psycholinguistic norms for 320 fixed expressions (idioms and proverbs) in French

Abstract: Hello Sandra, I am just back from a meeting. Thomas was there and, you know, he was all at sea. Well, he has been working hard these last days and All work and no play makes Jack a dull boy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 43 publications
(93 reference statements)
4
12
0
Order By: Relevance
“…The first result worth pointing out is the strong positive correlation between familiarity and the extent to which participants consider that they know the meaning of the idiom (knowledge). Such result is in line with other normative studies that have found moderate or strong positive correlations between these two variables [16,21,25,27], and suggests that the more familiar an idiom is rated, the more confident the speakers are in their knowledge of its meaning. However, in contrast to prior research [6,8,29], no correlation was found here between familiarity and the actual knowledge of the idiom meaning (knowledge_%, the percentage of participants who provided a correct definition of the meaning).…”
Section: Correlations Between Variablessupporting
confidence: 91%
See 1 more Smart Citation
“…The first result worth pointing out is the strong positive correlation between familiarity and the extent to which participants consider that they know the meaning of the idiom (knowledge). Such result is in line with other normative studies that have found moderate or strong positive correlations between these two variables [16,21,25,27], and suggests that the more familiar an idiom is rated, the more confident the speakers are in their knowledge of its meaning. However, in contrast to prior research [6,8,29], no correlation was found here between familiarity and the actual knowledge of the idiom meaning (knowledge_%, the percentage of participants who provided a correct definition of the meaning).…”
Section: Correlations Between Variablessupporting
confidence: 91%
“…Familiarity also showed a small negative correlation with length in words (see [6,25] for similar results), and a small positive correlation with predictability (see [5,8,16,21,25,27] for…”
Section: Correlations Between Variablesmentioning
confidence: 69%
“…For various languages, such as English (Titone and Connine, 1994;Libben and Titone, 2008;Bulkes and Tanner, 2017;Nordmann and Jambazova, 2017), French (Caillies, 2009;Bonin et al, 2013Bonin et al, , 2017, German (Citron et al, 2016), Italian (Tabossi et al, 2011) and Chinese (Li et al, 2016), norms have been published with the aim to increase the reliability of stimulus material in psycholinguistic studies on idioms. These norms provide a number of interesting measures, such as familiarity, decomposability, predictability or emotional valence, for several hundreds of items per language.…”
Section: Introductionmentioning
confidence: 99%
“…expressions: Bonin, Méot, Boucheix, & Bugaiska, 2018;Bonin, Méot, & Bugaiska, 2013), and, of course, words. Three important aims underpin the collection of norms.…”
mentioning
confidence: 99%